Bioethics : catastrophic events in a time of terror - Radest, Howard B., 1928-2014 (Lexington Books, 2009)
"Fire, flood, earthquake, famine, pestilence, and warfare are no strangers to our experience. Once, we sought to placate the gods who brought these evils upon us. Today, clinicians, engineers, and politicians replace priests, prophets, seers, and shamans, and we - Americans in particular - think to impose our will upon the world. In times of catastrophe, issues of good and evil surrender to rapid, nearly automatic, operational response. Yet the catastrophic event poses unavoidable moral choices, ones that are more politically and emotionally complex since 9/11 and our "War on Terrorism."" "This book benefits from the emergence of bioethics as it has evolved from its clinical roots to address policy, politics, and social practice far removed from that origin. At the same time, the clinical focus on narratives and cases provides a tangible center for ethical reflection. It reminds us that ethics is about persons and their choices, a perspective often lost to abstraction when ethics is left to the ministrations of academe. By treating the catastrophic event as both a category and a genre, Bioethics connects to aesthetics and so enables us to enrich ethical inquiry by ranging from pandemic, hurricane, and flood to terrorist attack."--Jacket